The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1029/gl016i008p00923
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interplanetary shocks on kilometric type III radio bursts

Abstract: Interplanetary (IP) type III bursts that undergo sudden intensity changes when their electron beams traverse the vicinity of an IP shock are examined. Three types of intensity changes are discussed: cutoffs in which the type III intensity is abruptly reduced and remains at the reduced level for all lower frequencies, narrow-band intensifications that frequently occur on the high-frequency edge of a cutoff, and narrow-band intensity reductions. Pitch angle scattering of the beam electrons in the enhanced magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…MacDowall (1989) observed that the flux of IP type IIIs changed suddenly as beams neared shocks. He suggested that the changes are caused by the scattering of beam electrons by magnetic turbulence.…”
Section: Discussionmentioning
confidence: 97%
“…MacDowall (1989) observed that the flux of IP type IIIs changed suddenly as beams neared shocks. He suggested that the changes are caused by the scattering of beam electrons by magnetic turbulence.…”
Section: Discussionmentioning
confidence: 97%
“…The type-III bursts (III 1 ) might then not start near the CME front, but at higher frequencies, and be interrupted by interactions of the electron beams with the turbulence near the front of CME 1 . This is a frequently quoted interpretation of complex features in type-III bursts, both at kilometric (MacDowall, 1989) and decametric wavelengths (e.g. Reiner and Kaiser, 1999).…”
Section: Evidence For Evolving Acceleration Regions In the Corona Durmentioning
confidence: 94%
“…This event also had local harmonic radio emission, Langmuir waves, and accelerated electrons observed upstream of the shock crossing at STEREO A [Graham and Cairns, 2015]. Produced by electron beams accelerated in solar flares, type IIIs can intensify as the beams cross the shock [Lacombe and Moller Pedersen, 1971;MacDowall, 1989;Li and Cairns, 2012], based on radio telescope triangulation measurements and theory. Interference from type III bursts, the almost vertical frequency-time signals in Figure 1, is apparent.…”
Section: Radio Theory and Observationsmentioning
confidence: 99%